Aspergillus-derived β-glucan nanoparticles: a dual strategy for Fusarium Wilt management and tomato plant growth enhancement - Ramalingam, Parthasarathy; Appu, Manikandan (Frontiers in Plant Science, 2025)
IntroductionA soilborne Ascomycete, Fusarium oxysporum f.sp. lycopersicum, is the causative agent of wilt disease, posing a significant threat to tomato plants and severely impacting global tomato production. Chemical fungicides are the primary strategy for controlling it. Employing fungicides arbitrarily and in huge dosages can pollute the environment and harm field workers and customers.MethodsTo combat tomato wilt, we synthesized β-glucan (isolated from the marine algal associate Aspergillus awamori) nanoparticles (β-glu-n) and evaluated their efficacy in promoting plant growth and suppressing Fusarium oxysporum.Results and discussionThe synthesized β-glu-n was confirmed using NMR and IR spectroscopy. The spherical shape with a smooth surface and average size of 35 ± 6.0 nm was observed by TEM. The hydrostatic zeta potential was -38.40 mV, indicating colloidal stability. The crystalline structure of the β-glu-n was confirmed by the XRD spectrum. Furthermore, a significant seed germination and growth profile, including higher shoot and root length and lateral root, was observed in the β-glu-n-treated tomato seeds count than in the mycelial glucan (m-β-glu) and control group under glasshouse conditions. Moreover, novel protein polypeptides were derived from β-glu-n-treated plants, indicating the increased photosynthetic rate. β-glu-n inhibited Fusarium oxysporum in a disc diffusion test and reduced wilt symptoms in under detached leaf assay. These results suggest that β-glucan nanoparticles can promote plant growth and prevent tomato wilt disease.